Análisis de los procedimientos administrativos y contables aplicados en la cooperativa de transporte intraprovincial "Rutas Empalmeñas". cantón El Empalme. periodo 2012 - Montoya Sánchez, Ángel Daniel (2013)
The present investigation project analyzes the administrative procedures and accountants of the COOPERATIVE OF INTRAPROVINCIAL OF PASSENGERS it TRANSPORTS “ROUTES EMPALMEÑAS”, during the period 2012; this work seeks to analyze from the administrative perspective and accountant the execution of the procedures that has the organization, for its execution; also this project the query of the main problem of the investigation responds. What administrative procedures and are accountants applied in the Cooperative of Transport Intraprovincial “Routes Empalmeñas?” The present investigation project is compound for two segments, the first one corresponds to the introductory part and the second to the chapters that constitute the body of the document in a number of five. This investigation consists on one side documental or theoretical and another practice. It is considered documental for that their objective was reached with the application of theories or advance of general order already existent and whose goods are known in the professional environment of the Accounting. It is considered practice because the necessary information, to achieve the outlined objective, was obtained directly of the reality. To develop the Theoretical Marco of the Investigation it became precise to analyze each one of the variables that are presented as a result of the position of the problem, it was necessary the search of opportune and truthful information in books, scientific articles, pamphlets and pages web that fulfilled the technical requirements characteristic of a scientific writing to my concept. As for the methodology of the investigation, methods like the inductive, deductive and analytic were used, since I consider that they are the most opportune when of executing an audit it is. As for the techniques, it became necessary to appeal to the interview, since it is the most direct method to obtain information on the part of the speaker. The execution of this work, included the evaluation of the administrative procedures and accountants applied in the Cooperative Intraprovincial of Transport of Fleeting Routes Empalmeñas, inside the evaluation it is analyzed in a detailed way the Manual of administrative Procedures and Accountants that it possesses the Cooperative, it is necessary to emphasize that this Manual this on approval from the year 2012, reason why it was of vital importance the evaluation of the same one. As essential part of this investigation project, they think about summations and recommendations in the Chapter V, these recommendations to my approach will contribute from an appropriate way to the administrative administration of the Cooperative Intraprovincial of Transport of Fleeting Routes Empalmeñas.